PENINGKATAN NILAI DAYA CERNA DAN ENERGI METABOLISME NITROGEN TERKOREKSI BIJI KACANG Vicia faba var. Diana MELALUI PENYINARAN DENGAN SINAR INFRA MERAH - Patuan L.P. Siagian (Research Center for Chemistry - LIPI, 1993)
Determination of the apparent digestibility by the difference method has been performed in order to ascertain the influence of infra-red treatment on the nutritional effect of legume seeds Vicia faba L. var. Diana. For the test, a total 0f 96 five-week old male chicks of LSL-Brown were kept in a full automatically adjustable climate conditioned room. The digestion test consisted of eight rations in mash form (1 basal ration and 7 test rations). The water was offered ad libitum. The duration of adaptation period was 4 days, the preliminary period was 3 days, and the main experimental period was 4 days, repective/y. The results of this experiment indicated a significant increase (p<0.05) of nutrient digestibility of legume seeds treated by infrared level 2 (80 seconds, seeds temperature 105°C) for dry matter (+14.6%), organic matter (+17.6%), starch (+16.5%), nitrogen free extract (+11.6%), lysine (+4.2%), threonine (+5.3%), and cystine (+11.9%). The value of nitrogen balance increased from 479,7 mg Niday to 622,3 mg Niday. An increase 0f N corrected meta-bolizable energy of the seeds from 10.67 MJ/kg DM to 11.95 MJ/kg DM was observed.